PEMANFAATAN TEKNOLOGI MELALUI LITERASI DIGITAL UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA DALAM KONTEKS SASTRA - Risma; Abel Widiastira; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the use of technology through digital literacy in improving students' language skills, especially in the context of literature learning. This study uses a qualitative descriptive approach with a literature study method to explore the use of digital media such as podcasts and Wattpad. Data were obtained from literature reviews and relevant previous research results. The results of the study show that digital technology, especially through digital literacy, plays an important role in supporting the development of four language skills: listening, speaking, reading, and writing. Podcasts have proven effective in improving listening and speaking skills, while Wattpad encourages students' interest in reading and creative writing skills. Digital literacy also makes a positive contribution to students' ability to filter information, think critically, and communicate effectively in the digital era. Digital media integration is important to improve students' language competency.